Extraction of Indium from Zinc Sulphide Concentrates - Javad Koleini, S.M.; Saberian, K.; Abdolahi, M.; Mehrpouya, H. (Asian Journal of Chemistry, 2010)
A new process for extraction of indium from zinc sulphide concentrates containing very low amount of indium was proposed. In this process, after dissolution of indium from neutral leached residue, indium precipitates from solution selectively to prepare indium concentrate solution for solvent extraction by bis(2-ethylhexyl)phosphoric acid (D2EHPA). The technologies in the processes, such as neutral leaching, leaching the neutral leached residues with high concentrated acid at high temperature and reduction of ferric ion to ferrous ion, selective precipitation of indium, solvent extraction and cementation of indium were investigated. The results show that total recovery ratio of indium from zinc sulphide concentrates containing very low amount of indium is increased from 50 % to 90 %.